(untitled) (Nóema, 2021)
The paper aims at outlining some essential Neoplatonic traits in order to accomplish an ecological Metaphysics, by developing a dynamic and intensive notion of «Selfness» within three main fields of knowledge: Biology, Psychology, Cosmology. Starting from post-cybernetics systems’ theories, by deepening Bateson’s Ecology of Mind, in the end the research will restore the ancient One-Many aporia, showing its irrefutable value.